Competitive heterogeneity, cohorts, and persistent advantage - Madsen, Tammy L.; Walker, Gordon (Strategic Management Journal, 2017)
Research summary: Juxtaposing competing theories of whether superior profits endure, this article investigates differences in the rates at which firms' profit advantages persist following a significant regulatory change in the rules governing industry competition. Such a change creates two cohorts of firms, Entrants that lack experience in the industry and Incumbents that competed in the industry before the regulatory shift. The findings show that both cohorts' profit advantages persist, but at different rates: Superior performing Incumbents sustain an advantage longer than superior performing Entrants. This result is counterintuitive since Entrants are not constrained by a legacy of competing under the prior regime. Overall, the findings indicate that stages of a firm's development and of an industry's evolution are critical to understanding how long superior profits persist . Managerial summary: State and federal institutions employ regulations in an attempt to address market failures and to create a stable set of market and nonmarket relationships among relevant actors. A byproduct of this stability is decreased competition, and in turn, reduced incentives for firms to develop efficient operations. One might expect then that deregulation would fundamentally disrupt incumbent firms' abilities to develop and sustain a profit advantage. We find the reverse: Over time, some firms in the Incumbent cohort develop persistent, albeit temporary, profit advantages despite an onslaught of Entrants. Thus, while deregulation shakes out inefficient firms, it may strengthen, rather than threaten the profit trajectories of incumbent firms over time. Advantages developed by superior performing Entrants also endure, but for a shorter duration relative to Incumbents . Copyright © 2015 John Wiley & Sons, Ltd.